Planungskultur - eine Bestandsaufnahme. - Reimer, Mario (Routledge, 2016)
Der Beitrag behandelt die vielschichtigen Diskurse und unterschiedlichen Sichtweisen von Planungskultur in Wissenschaft und Forschung in Form einer chronologischen Übersicht. Er skizziert zukünftige Herausforderungen der Planungskultur-Forschung, in der insbesondere die analytische Perspektive auf Planungskultur mitsamt ihrer Methodologien und Methoden eine tragende Rolle spielt.

Research on planning cultures seems to be in vogue. This article strives for a critical discussion of the term and concept of planning culture, its basic premises and meanings as well as its historical roots in planning literature. It argues for a clearer theoretical and conceptual foundation of the term and hence directly addresses its benefits for planning research. At the core of this article is the identification of different discourses on planning culture that took place during the last five decades in planning theoretical debate. Culture was first introduced into the planning debate after the death of purely rational models and interpretations of planning in the 1960s. Later it was addressed indirectly in studies concerning values and norms of planners, especially in the 1980s, followed by some comparative work on planning systems and planning cultures since the 1990s. At the same time, the term planning culture was conceived as a normative expression of good planning because culture itself was construed as something good. Only very recently has the analytical potential for planning research been at the core of the debate. Nonetheless, the methodological premises of planning cultural research have not yet been discussed, and merit future debate across disciplines.
Planning culture - historical roots, present state and future challenges.
Keywords: Planung; Theorie; Raumplanung; Stadtplanung; Planungsprozess; Planungstheorie; Bestandsaufnahme; Forschungsmethode; Forschungsstand; Planungskultur; Begriff; Chronologie; Planungsgeschichte; Verwaltungsforschung